Understanding and Supporing Knowledge Work in Everyday Life - Grabill, Jeffrey T.; Hart-Davidson, William (Language at Work - Bridging Theory and Practice, 2007)
Our purpose in writing is two-fold: (1) to introduce this audience to the Writing in Digital Environments (WIDE) Research Center, and (2) to make an argument about the importance of understanding and supporting knowledge work for professional and technical communicators. We are particularly interested in what knowledge (writing) work looks like in multiple contexts—for instance, in civic organizations as well as in corporate organizations— because contemporary social and community contexts are dependent on high-quality knowledge work. This explains our interest in “everyday life.”